Group Investigation (GI) Model to Improve Learning Outcomes in Speaking Aspect - Lehan, Denitrius Nong (STKIP Harapan Bima, 2022)
The main problem raised in this Classroom Action Research is the low English learning outcomes achieved by grade VIII students of SMPN Satap Wolomapa in the aspect of speaking in English. This research was carried out at SMPN Satap Wolomapa in grade VIII, school year 2022/2023 with a total of 15 students. This research is carried out in two cycles, each cycle in research includes four steps, namely (1) planning, (2) implementation (acting), (3) observation (observing), (4) reflection (reflecting). The results obtained in this study are: 1) Results in cycle I have an average value of 79, 2) Learning Completeness in cycle I of 78%, 3) Results in cycle II have an average value of 79, and 4) Learning Completeness in cycle II of 100%. Based on research data and discussion, it can be concluded that applying the Group Investigation (GI) model to English subjects can improve classroom learning outcomes